Gods in Disorder - McCauley, Robert N.; Graham, George (Journal for the Cognitive Science of Religion, 2021)
Commentators’ concerns occasion clarifications of positions in Hearing Voices and Other Matters of the Mind. Philosophical naturalism holds that philosophers needlessly handicap their projects if they ignore the sciences. Ecumenical Naturalism maintains that similar forms of cognition and experience associated with religiosity and mental disorders may submit to similar scientific explanations. The by-product theory, which looks to the operations of maturationally natural cognitive capacities to explain religious representations’ forms, offers explanatory leverage with regard to some mental disorders. The fact that examples are mostly American, Christian, and Western need not preclude the accounts’ broader applicability. Explanatory pluralism endorses many explanatory approaches. The aim is only to show how much cognitive considerations can do, not to suggest that they provide comprehensive theories of anything. Other telling proposals will enhance understanding of these matters. The operations of maturationally natural dispositions, regardless of how they are cued, contribute to what humans take to be meaningful.